(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The main problem raised is how was social and cultural life of Chinese ethnic in Padang City from the New Order to the beginning of the reformation. From this problem, three research questions are revealed: 1) How was the socio-cultural life of Chinese ethnic in Padang city since the early period of 1966. 2) What were the efforts made by the Chinese in Padang city to preserve their ethnic identity in socio-cultural aspect during 1967-2002. 3). How is the pattern of cultural interaction between Chinese ethnic and residents in Padang city. The method used to explain these problems is historical methods: source collection, source criticism, interpretation, and historiography. The research techniques used are literature study and interviews. The findings conclude that the socio-cultural life of Chinese ethnic experienced ups and downs depending on the implemented policies in each period of the Indonesian government. However, the results of the study found out that the socio-cultural life of Chinese ethnic in Padang city can still be carried out following the traditions and cultures of their ancestors. It is because the community and the city government provided spaces for Chinese ethnic as a form of acculturation so that the similarities between Chinese ethnic and the Minangese people in preserving culture could be implemented based on respective cultures and traditions In Chinese arts membership, it was found that there was a cooperation between Chinese and Minangese community in Barongsai art and also other arts a form of cultural acculturation.